2014
DOI: 10.1002/ajh.23823
|View full text |Cite
|
Sign up to set email alerts
|

The choice of second‐line therapy in steroid‐resistant immune thrombocytopenia: Role of platelet kinetics in a single‐centre long‐term study

Abstract: *Splenectomy is a time-honoured well established approach for patients with steroid-resistant immune thrombocytopenia (ITP). However, due to the more recent availability of therapeutic options alternative to splenectomy, such as rituximab and agonists of the thrombopoietin-receptor, the choice of second-line therapy is challenging. Platelet kinetics has been widely used to predict response to splenectomy. We describe the outcome of 70 chronic ITP patients who performed a platelet kinetic study after failure of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 17 publications
1
36
0
2
Order By: Relevance
“…193 Indium-labeled autologous platelet scanning may be able to predict response to splenectomy but is not widely available. [198][199][200][201] OPEN VS LAPAROSCOPIC SPLENECTOMY. Laparoscopic splenectomy is associated with significantly shorter hospitalization, less intraoperative blood loss, and quicker resumption of oral diet compared with open splenectomy (evidence levels IIb-III).…”
Section: Laparoscopic Splenectomy Is As Effective As Openmentioning
confidence: 99%
“…193 Indium-labeled autologous platelet scanning may be able to predict response to splenectomy but is not widely available. [198][199][200][201] OPEN VS LAPAROSCOPIC SPLENECTOMY. Laparoscopic splenectomy is associated with significantly shorter hospitalization, less intraoperative blood loss, and quicker resumption of oral diet compared with open splenectomy (evidence levels IIb-III).…”
Section: Laparoscopic Splenectomy Is As Effective As Openmentioning
confidence: 99%
“…Autologous 111 Indium-oxinate-labelled platelet sequestration study in patients with immune thrombocytopenia treated by thrombopoietin receptor-agonists An increasing number of patients treated with thrombopoietin receptor-agonists (TPO-Ras) for immune thrombocytopenia (ITP) are reluctant to undergo splenectomy mostly because of the irreversibility of the procedure and concerns about its long-term safety (Kojouri et al, 2004;Boyle et al, 2013;Thai et al, 2016). Isotopic assessment of the site of platelet destruction using autologous 111 Indium-oxinatelabelled platelet kinetic study might help to determine whether or not splenectomy is indicated in these patients (Najean et al, 1997;Sarpatwari et al, 2010;Palandri et al, 2014). The interpretation of the isotopic study results depends on the expertise in the labelling procedure and on the response criteria used (Navez et al, 2015 (Najean et al, 1997).…”
Section: Supporting Informationmentioning
confidence: 99%
“…production is not sufficient to overcome the platelet destruction by the immune system. The role of platelet sequestration isotopic study as a predictive factor of short and long-term response to splenectomy has been challenged by divergent reports or reviews (Navez et al, 2015), whereas three large independent studies have found a significant association with between purely or predominantly splenic pattern of platelet sequestration (Najean et al, 1997;Sarpatwari et al, 2010;Palandri et al, 2014). The distribution pattern of platelet splenic sequestration was similar in patients receiving TPO-RAs and untreated patients.…”
Section: Referencesmentioning
confidence: 99%
“…In patients considering splenectomy, I refer them for an indium‐labelled ‐platelet sequestration scan. Patients with predominant splenic sequestration appear to have better responses (approximately 90%), compared to patients with mixed liver and spleen destruction who have a 40% chance of remission (Sarpatwari et al , ; Palandri et al , ).…”
Section: Managementmentioning
confidence: 99%